Baker's Kingdom - Mojitol, Hosean; Naflan, Nurul Syahirah; Shahrul Nizam, Salwa Liyana (2018)
Baker's Kingdom is about selling brownies and provided services which is operating small cafe that included serving hot and cold beverages. Our business that located at Jalan Gaya, Pusat Bandar Kota Kinabalu, 88999 Kota Kinabalu, Sabah. While there are many shops and cafe selling baking pastry product, Baker's Kingdiom will get through the competitors due to its unique and excellent detail regarding our customers, our business will slowly increase and surely gain market share as it provides excellent goods and services to customer thus can build strong relationship between the customers and our business. Furthermore, we believe that our business will successfully compete with the competitors in a few years ahead. We, Baker's Kingdom saw the opportunity that our business has the potential of success as people want difference in baking and pastry industry and that is what we offered.